(untitled) (Boca Raton, 2014)
The use of organic management practices in field cropping continues to rise globally, and these methods have proven to be a viable way to produce food with reduced resource use and environmental damage. Managing Energy, Nutrients, and Pests in Organic Field Crops challenges the popular misconception that organic systems are weak at managing energy, nutrients, and pests and shows how innovative farm designs can enhance organic performance. It provides information for assessing the current state of knowledge on organic field cropping and for making the systems more viable.
Keywords: Nông nghiệp và năng lượng,Organic farming,Agriculture and energy,Plant nutrients,Pests; Control